A priori-defined diet quality indexes and risk of type 2 diabetes: the Multiethnic Cohort - Jacobs, S.; Harmon, B.; Boushey, Carol; Morimoto, Y.; Wilkens, L.; Le Marchand, L.; Kröger, J.; Schulze, M.; Kolonel, L.; Maskarinec, G. (Springer Verlag, 2015)
Aims/hypothesis: Dietary patterns have been associated with the incidence of type 2 diabetes, but little is known about the impact of ethnicity on this relationship. This study evaluated the association between four a priori dietary quality indexes and risk of type 2 diabetes among white individuals, Japanese-Americans and Native Hawaiians in the Hawaii component of the Multiethnic Cohort.Methods: After excluding participants with prevalent diabetes and missing values, the analysis included 89,185 participants (11,217 cases of type 2 diabetes). Dietary intake was assessed at baseline with a quantitative food frequency questionnaire designed for use in the relevant ethnic populations. Sex- and ethnicity-specific HRs were calculated for the Healthy Eating Index-2010 (HEI-2010), the Alternative HEI-2010 (AHEI-2010), the Alternate Mediterranean Diet Score (aMED) and the Dietary Approaches to Stop Hypertension (DASH).Results: We observed significant inverse associations between higher DASH index scores and risk of type 2 diabetes in white men and women, as well as in Japanese-American women and Native Hawaiian men, with respective risk reductions of 37%, 31%, 19% and 21% (in the highest compared with the lowest index category). A higher adherence to the AHEI-2010 and aMED diet was related to a 13–28% lower risk of type 2 diabetes in white participants but not in other ethnic groups. No significant associations with risk of type 2 diabetes were observed for the HEI-2010 index.Conclusions/interpretation: The small ethnic differences in risk of type 2 diabetes associated with scores of a priori-defined dietary patterns may be due to a different consumption pattern of food components and the fact that the original indexes were not based on diets typical for Asians and Pacific Islanders.